The impact of supplier partnerships on quality of information sharing, commitment, trust and supply chain performance in the automotive industry - Siphesihle Nokwanda Mthiyane; Osayuwamen Omoruyi; Elizabeth Chinomona (Journal of the Academy of Business and Emerging Markets)
The South African automotive industry is continually under threat of not achieving sustainable supply chain performance. Factors negatively affecting this industry include the low quality of the information shared, inadequate commitment and trust among supply chain participants, and the country's poor economic performance. The purpose of this study is to analyze the relationship between supplier partnership, quality, information sharing, commitment, trust, and supply chain performance in the South African automotive industry. Data analysis techniques include descriptive and inferential statistics. The results of the research study show positive relationships between the study variables, namely, supplier partnership, quality of information sharing, commitment, trust, and supply chain performance. The quality of information shared among the supplier partners has the most significant impact on the commitment. This suggests that continuous improvement of information quality can lead to better synchronization of supply and demand in the automotive supply chain.